PEMBUATAN AKTA RELAAS PADA RAPAT UMUM PEMEGANG SAHAM PERUSAHAAN NON TBK MELALUI TELEKONFERENSI - M Jordan Pradana; Fauzi Syam; Syamsir Syamsir (Jurnal Indragiri Penelitian Multidisiplin, 2022)
The General Meeting of Shareholders (GMS) can be held via video telekonferensi and other electronic media facilities based on Article 77 paragraph (1) of the Law on Limited Liability Companies (UUPT). In this case, it has been regulated in Law Number 40 of 2007 concerning Limited Liability Companies and OJK Regulation Number 16 of 2020. However, the UUPT and POJK only regulates tbk companies, and does not regulate non-tbk companies, and does not explain the mechanism of the GMS. electronically. The aims of this research are: (1) To find out the arrangement for the implementation of the General Meeting of Shareholders of a Non Public Company through Telekonferensi in the perspective of legislation. (2) To find out the mechanism for the implementation of the General Meeting of Shareholders of a Non-Public Company and the form of the Deed of Minutes of Meeting by Telekonferensi.”